Optic nerve head sarcoidosis mimicking an intraocular tumour, and occurring as the first manifestation of neuro-ocular sarcoidosis - Krishna, Yamini; Christou, Louise; Khzouz, Jakub; Hussain, Rumana; Heimann, Heinrich; Coupland, Sarah E. (American journal of ophthalmology case reports, 2020)
Sarcoidosis is a chronic idiopathic granulomatous inflammatory disease that can affect many major organ systems, primarily the lungs, and hence has remarkable clinical heterogeneity. At least 50% of patients with systemic sarcoidosis develop inflammatory eye disease, and in approximately 21% of cases, it may be the first clinical manifestation. Neuro-ocular involvement occurs in <3% of all sarcoidosis cases, and rarely involves the optic nerve. We describe an unusual case of an intraocular sarcoidosis presenting as an unclear optic nerve mass. A 61-year-old male presented with painful gradual visual loss in the right eye. Previous history included Stage II Hodgkin lymphoma (HL) and concurrent mediastinal sarcoidosis, both in remission 5 years later. On examination, the right eye (RE) vision had no light perception, neovascular glaucoma, attenuated retinal vessels and a non-pigmented optic disc mass. The left eye was normal. The RE showed no response to oral steroids, was painful due to neovascular glaucoma and the concerns of recurrent HL with intraocular manifestations lead to RE enucleation. Macroscopic examination revealed a whitish mass at the optic disc, which histomorphologically showed a non-necrotising granulomatous inflammation consuming the optic nerve head and extending into the optic nerve resection margin. Special stains for microorganisms were negative. The uveal tract was free of inflammation. The morphological features were consistent with optic nerve sarcoidosis. A diagnosis of neuro-ocular sarcoidosis was made, and the patient was commenced on infliximab. Neuro-ocular sarcoidosis is known as the ‘great imitator’ because it can cause a variety of non-specific clinical signs and symptoms, mimicking many other conditions, including lymphomas. Intraocular sarcoidosis is not unusual and typically affects the uvea. Isolated optic nerve sarcoidosis is rare. The challenging aspect of intraocular sarcoidosis is the requirement of prompt treatment to reverse any eye damage and prevent permanent visual loss. Here, optic nerve sarcoidosis was very advanced, and was associated with intracerebral manifestations. Neuro-ocular sarcoidosis is a difficult condition to diagnose and treat. Our case was complicated by the previous history of HL and concurrent mediastinal sarcoidosis which were in remission. In patients with a history of sarcoidosis with new loss of vision and neurological weaknesses oculocerebral involvement must be included in the differential diagnosis even in the absence of typical manifestations of ocular sarcoidosis as in uveal tract involvement. •Optic nerve head (ONH) sarcoidosis without uveal tract involvement is rare.•ONH sarcoidosis can be the first manifestation of systemic sarcoidosis.•ONH sarcoidosis may be the first manifestation of neuro-ocular sarcoidosis.•ONH masses present diagnostic challenges due to the impact of tissue biopsy.•‘Sarcoid-like’ reaction or sarcoid-lymphoma syndrome may occur with concurrent lymphoma.